The Effect Of Job Satisfaction Mediating Organizational Culture And Compensation On Job Loyalty In Generation Z - Nikmah, Wasilatun; Anggarini, Desy Tri; Armaniah, Henny (Jurnal Scientia, 2024)
This research aims to determine the mediating effect of job satisfaction on the influence of organizational culture and compensation on work loyalty. This research method is quantitative descriptive. This research used a sample of 97 respondents by distributing online questionnaires. This research uses a Structural Equation Modeling (SEM) approach based on Partial Least Square (PLS) using SmartPLS 3.3 software. This research is census research. The research results show that all indicators used in this research are valid and reliable. Conclusion,Organizational culture, compensation and job satisfaction influence work loyalty. Also, job satisfaction has a role in mediating the influence of compensation on work loyalty. However, it does not mediate the influence of organizational culture on work loyalty.